Multifocal Head and Neck Neurofibromas with Osseous Abnormalities and Muscular Hypoplasia in a Child with Neurofibromatosis: Type I - Rachna Rath; Sheetal Kaur; Shadab Ali Baig; Punyashlok Pati; Sonalisa Sahoo (Case Reports in Radiology)
Neurofibromatosis type 1 (NF1) is a clinically and genetically distinct disease involving both neuroectodermal and mesenchymal derivatives. Orofacial manifestations in NF1 have been documented before but occurrence of multifocal intraosseous (IO) and extraosseous (EO) neurofibromas is rare. The present case highlights the importance of imaging findings in the diagnosis and management of multifocal jaw, infratemporal, and parotid neurofibromas with muscular hypoplasia in an eight-year-old girl with NF1. Apart from orthopantomograms (OPG), three-dimensional computed tomography (3D CT) and cross-sectional reformations were valuable in delineating the extent of the lytic lesion and identifying additional bony deformities of the mandible. Magnetic resonance imaging (MRI) helped to identify the solid nature of the lesion and true extent of the soft tissue mass.